King size or all size: Proposing a typology of amplification translation technique for children picturebook translation - SF. Luthfie Arguby Purnomo; Lilik Untari; SF. Lukfianka Sanjaya Purnama; Nur Asiyah; Muhammad Zainal Muttaqien; Robith Khoiril Umam; Yustin Sartika; Umi Pujiyanti; Hidayatul Nurjanah (Universitas Syiah Kuala, 2020)
The necessity for a children’s picturebook to generate a proairetic decoding by the children influences translators to deliver the messages of the source text as explicit as possible. This condition leads the translators to implement amplifications aimed at detailing particular information. Though a proairetic reading is achieved through amplification, negative impacts follow the implementation. This qualitative experiential study involves nine children picturebook translators. Exchanging insights and translated texts in a focused group discussion (FGD) comprising of English to Indonesian and English to Javanese children picturebook translators, we found that a typology of amplification technique constructed specifically for children picturebook translation is required to provide a guideline for the translators when forced to apply amplification. The result of the translation data, supported by FGD, indicates that amplification is classifiable into three function-based types namely naturalizing, synchronizing, and stylizing amplifications. These amplifications, when applied, generate four impacts namely congruity losses, effect rendering, reading level deviation, and deviation on the purposes of the children’s picturebooks. These impacts deal with verbosity and thus requiring a further concern on verbosity level acceptance.